Emergency airway management in a patient with facial trauma: Combining clinical judgment and skill with fortuity (Indian Journal of Case Reports, 2024)
Airway management in maxillofacial trauma is a challenging task. Distorted anatomy leading to difficult face mask ventilation and intubation requires clinical expertise in emergency scenarios. Planning and managing such challenging airways in a timely manner requires the utmost cooperation from the patient. Here, we present a case of self-inflicted facial gunshot injury that was posted for surgical tracheostomy followed by facial wound exploration and repair. Uncooperative behavior and irritability of the patient were toppings to the difficult airway, however, timely clinical judgment and replanning according to the case requirement contributed to the successful airway management during emergency hours.